2003
DOI: 10.1051/0004-6361:20031087
|View full text |Cite
|
Sign up to set email alerts
|

Time of flight mass spectra of ions in plasmas produced by hypervelocity impacts of organic and mineralogical microparticles on a cosmic dust analyser

Abstract: Abstract. The ionic plasma produced by a hypervelocity particle impact can be analysed to determine compositional information for the original particle by using a time-of-flight mass spectrometer. Such methods have been adopted on interplanetary dust detectors to perform in-situ analyses of encountered grains, for example, the Cassini Cosmic Dust Analyser (CDA). In order to more fully understand the data returned by such instruments, it is necessary to study their response to impacts in the laboratory. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 42 publications
8
70
0
Order By: Relevance
“…Experimental impact by grains of 1 mm and smaller grain size, of appropriate physical properties and at tightly constrained velocity, is much more difficult with LGG and is limited to electrically conductive materials in electrostatic Van de Graaff accelerators [16]. Monodispersive spheres of a size range suitable for LGG calibration shots must also yield identifiable impact residue, so that craters made by the nominal projectiles can be distinguished from fine gun-derived debris, precluding many polymer and ferrous metal projectiles.…”
Section: Refining the Interpretation Of Crater Size And Shape Measurementioning
confidence: 99%
“…Experimental impact by grains of 1 mm and smaller grain size, of appropriate physical properties and at tightly constrained velocity, is much more difficult with LGG and is limited to electrically conductive materials in electrostatic Van de Graaff accelerators [16]. Monodispersive spheres of a size range suitable for LGG calibration shots must also yield identifiable impact residue, so that craters made by the nominal projectiles can be distinguished from fine gun-derived debris, precluding many polymer and ferrous metal projectiles.…”
Section: Refining the Interpretation Of Crater Size And Shape Measurementioning
confidence: 99%
“…Polypyrrole (PPy) is an attractive one among the family of conductive polymers because of its associated electrical, electrochemical, and optical properties, coupled with excellent environmental stability. Such hybrid materials combine metallic-like conductivity with the processability of conventional polymers, which hence present them as potential materials suitable for applications in versatile fields such as electrochemical sensors, optoelectronic devices, and space science [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experiments using van de Graaff accelerators have demonstrated that organic molecules survive high velocity impacts, are ionized and can then be detected by mass spectroscopy (Goldsworthy et al, 2003;Srama et al, 2004Srama et al, , 2009). In these experiments, polystyrene cores were covered with a conductive polypyrrole or polyaniline coating, so that they could be charged and accelerated in the van de Graaff accelerator.…”
Section: Discussionmentioning
confidence: 99%
“…The impacts varied in speed from 5 km s À1 to almost 20 km s À1 . The resulting spectra showed series of peaks corresponding to carbon clusters that were fragments of the original particles, depending on the impact velocities (Goldsworthy et al, 2002(Goldsworthy et al, , 2003. Solid aliphatic microparticles have also been used in electrostatic accelerator experiments and again show survival of carbon clusters (e.g.…”
Section: Discussionmentioning
confidence: 99%